Entrepreneurship Business Education Capabilities in Emerging Poverty Alleviation Programme in Nigeria - Ordu, Pac; Naboth-Odums, A (Mediterranean Journal of Social Sciences, 2012)
The paper discussed to unveil the economic potentials in business education programme with emphasis oneducational and employability capabilities. Inspite of the high unemployment rate of graduates, somescholars have encouraged effective implementation of business education curriculum objectives. The papermade extensive use of these scholarly opinions that derive their basis from national education policy,NCCE business education objective and the SIWES curriculum. The paper concluded that businesseducation programme curriculum has the capability of enhancing graduate self-employment to reduceincidences of graduate unemployment in the country. The paper saw the importance of professionallyqualified business educators to teach and administer their programme for effective growth anddevelopment. It was recommended among others that the challenge of quality business educationteachers need to be pursued with zeal to eliminate the presence of interlopers.